Current methodological approaches assessing the healthrelated risks assessment in manned spaceflight missions - A. V. Lobanov; E. D. Makeeva; D. O. Meshkov; S. A. Ponomarev; S. N. Cherkasov; A. F. Pashchenko; Yu. V. Sidelnikov (Informaciâ i Innovacii)
Further development of manned space exploration requires appropriate scientific and appropriate modern methodological approaches assessing the health risks of participants in missions to an orbital station with high inclination of the orbit and interplanetary missions. The "Environmental Scanning" as well as available Internet sources (PubMed and EMBASE; 198 relevant publications) and personal messages, followed by expert discussion within the framework of an interdisciplinary working group were used to assess the contemporary approaches of manned spaceflight risk definition, classification, assessment and management. The results indicated that the term "risk" itself needs to be clarified, and mathematical models based on modern approaches other than differential calculus and providing expert support for management decisions should be developed or adapted to available evidence-based real-world data obtained in experiments using laboratory animals, ground-based simulation studies with the participation of volunteers, as well as during pre- and post-flight examinations of astronauts. It is advisable for this purpose to use interdisciplinary and interdepartmental working groups, including experts in the field of aviation, space and marine medicine, public health and health organization and control sciences as well as contemporary mathematical methods of analysis and statistics.